1992
DOI: 10.1017/s0021859600071562
|View full text |Cite
|
Sign up to set email alerts
|

Ratios of plant to soil concentrations of strontium-85 and their relation to exchangeable bases for soils and crops of Greece

Abstract: The relationship between values of 85 Sr concentration ratios (CRs) and exchangeable bases, expressed in absolute (mmol/kg) or relative (percentage of cation exchange capacity (CEC)) terms, was considered using the results of a glasshouse pot experiment conducted in 1989, for soils and crops of Greece. Exchangeable calcium, expressed in mmol/kg, presented, in most instances, a significant (P = 005-001) or highly significant (P < 001) negative correlation with the CRs of various crops or plant parts, while exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
(6 reference statements)
0
6
1
Order By: Relevance
“…The disagreement of the results of our work with some of the results reported by Papanicolaou et al (1991Papanicolaou et al ( , 1992a must be attributed to the soils used. All soils used by Papanicolaou et al were inorganic.…”
Section: T H E Absolute Values Of Correlation Coefficientscontrasting
confidence: 96%
See 3 more Smart Citations
“…The disagreement of the results of our work with some of the results reported by Papanicolaou et al (1991Papanicolaou et al ( , 1992a must be attributed to the soils used. All soils used by Papanicolaou et al were inorganic.…”
Section: T H E Absolute Values Of Correlation Coefficientscontrasting
confidence: 96%
“…and to Ca in both extractable form or in the soil solution but not to pH neither to Ca and Ca + Mg, expressed as proportions of C.E.C., as Papanicolaou et al (1991Papanicolaou et al ( , 1992a were found for inorganic soils. and to Ca in both extractable form or in the soil solution but not to pH neither to Ca and Ca + Mg, expressed as proportions of C.E.C., as Papanicolaou et al (1991Papanicolaou et al ( , 1992a were found for inorganic soils.…”
Section: O N C L U S I O N Smentioning
confidence: 71%
See 2 more Smart Citations
“…Sr were found to vary with soil type and be correlated with several soil properties for various crops or plant parts (Papanicolaou et al 1991). Their correlation with exchangeable (Ca + Mg) or with total exchangeable bases (Papanicolaou et al 1992) was very good (r from -0-87 to -0-92) and, on average, better than that of exchangeable Ca (r from -0 8 3 to -0-86).…”
Section: S5mentioning
confidence: 96%